2013
DOI: 10.2139/ssrn.2325390
|View full text |Cite
|
Sign up to set email alerts
|

Job Mobility, Peer Effects, and Research Productivity in Economics

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 54 publications
1
10
0
1
Order By: Relevance
“…The number of transnational job changes positively affects research output and multidisciplinarity, which aligns with the literature that underlines the relevance of transnational mobility for research activities and production (Fangmeng, ; Filippo et al, ; Jonkers & Tijssen, ; Yamashita & Yoshinaga, ), and suggests that transnational mobility remains important in today's academia despite the greater frequency of virtual mobilities permitted by advances in ICT (Bolli & Schlapfer, ). The mobility variables associated with the educational path are not significant, which may indicate that mobility can be influential right after the conclusion of education and entry into the labour market, but not later.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…The number of transnational job changes positively affects research output and multidisciplinarity, which aligns with the literature that underlines the relevance of transnational mobility for research activities and production (Fangmeng, ; Filippo et al, ; Jonkers & Tijssen, ; Yamashita & Yoshinaga, ), and suggests that transnational mobility remains important in today's academia despite the greater frequency of virtual mobilities permitted by advances in ICT (Bolli & Schlapfer, ). The mobility variables associated with the educational path are not significant, which may indicate that mobility can be influential right after the conclusion of education and entry into the labour market, but not later.…”
Section: Resultssupporting
confidence: 80%
“…While acknowledging the relevance of transnational mobility, Ackers () suggested that mobility should be understood more broadly and include sectoral mobility, interdisciplinary mobility, transdisciplinary mobility and virtual mobility as well as mobility between public and private sectors. Heeringen and Dijkwel () and Bolli and Schlapfer () highlighted the relevance of job mobility from one organisation to another within and across a country as important with regards to networking, experiencing new ideas and adjusting to new environments. Job mobility is entangled with transnational mobility and is observed mostly in academics who move from the peripheries to the centres of scientific power and academic prestige (Bennion & Locke, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…with the effects of a researcher's change of affiliation within one country -in an attempt to find out more about the underlying mechanisms that make appointment committees appreciate international mobility in comparison to national mobility. In so doing, we are the first to analyze a potential direct link between a researcher's national mobility and his or her appointment success -over and above the effect national mobility might have on a researcher's publication record (for the latter see e.g., Bäker (2015); Bolli and Schläpfer (2015); Fernández-Zubieta, Geuna, and Lawson (2015)). …”
Section: Time To Go? (Inter)national Mobility and Appointment Successmentioning
confidence: 99%